Analisis Perkembangan Kemampuan Keuangan Daerah Dalam Mendukung Pelaksanaan Otonomi Daerah di Kabupaten Karo - Nabilah Denisa; Dito Aditia Darma Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the development of the financial capacity of Karo Regency in supporting the implementation of regional autonomy. The method used is descriptive qualitative with a case study approach. Data were obtained through interviews, observations, and documentation, and analyzed using source triangulation techniques and financial ratio analysis, including The Regional Financial Dependency Ratio, Regional Financial Independence Ratio, and the Effectiveness Ratio of Locally Generated Revenue (PAD). The results of the study indicate that the contribution of PAD remains relatively low, reflecting a high dependency of Karo Regency on central government transfers. The study concludes that in order to enhance regional financial capacity, it is necessary to optimize local revenue sources, reduce reliance on central transfers, and align financial management strategies with the goals of sustainable regional development.